1977
DOI: 10.1007/bf00146430
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of plasma wave electric fields in solar flares

Abstract: Measurements of electric fields in solar flares using the Stark effect exhibited by neutral helium atoms are reported. Electric field strengths as high as 700 V cm -1 are observed. Measurements of electron densities indicate that the electric fields originate from nonthermal plasma waves. Analysis of the plasma wave fields coupled with plasma density and temperature measurements indicate that the Lower Hybrid Drift instability may be present in the flaring region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Even more intensive electric fields (up to 700 V/cm) were measured by Davis. 25 Moreover, Foukal et al, 26 while analyzing two eruptive events, have found that the total electric field in such structures is less than 10 V/cm and about 40 V/cm in a post-flare loop.…”
Section: A Torsional Spine Reconnectionmentioning
confidence: 98%
“…Even more intensive electric fields (up to 700 V/cm) were measured by Davis. 25 Moreover, Foukal et al, 26 while analyzing two eruptive events, have found that the total electric field in such structures is less than 10 V/cm and about 40 V/cm in a post-flare loop.…”
Section: A Torsional Spine Reconnectionmentioning
confidence: 98%
“…A formula for the "mean particle field" given by Griem (Griem 1974, p. 22) had been used by ourselves and by some other authors in this context (e.g., Jordan et al 1980, Davis 1977. This formula was found to lead to a field intensity estimate about 3.5 times as high, for a given observed broadening, as the .…”
Section: *"mentioning
confidence: 94%
“…Wien (1916) is the first author who pointed out the possibility of measuring electric field of solar plasma and measured the motional electric field using Stark effect. Around 1980s, some attempts to measure the electric field with helium and silicon spectra had been made, which suggested an electric field of 700 V/cm (Davis 1977) and 300 V/cm (Jordan et al 1980) respectively. Even so, Moran & Foukal (1991) pointed out that direct measurement of the electric field by Stark effect is hard to operate with the low sensitivity.…”
Section: Introductionmentioning
confidence: 99%